Qorimayus, a new genus of relictual, high-altitude harvestmen from western Argentina (Arachnida, Opiliones, Gonyleptidae) reveals trans-Andean phylogenetic links - Acosta, Luis E. Acosta (Zootaxa, 2020)
A new genus of Gonyleptidae Pachylinae, Qorimayus gen. nov., is described to place the high-altitude species originally named Parabalta alticola Ringuelet, endemic to Sierra de Famatina, western Argentina. While classical exomorphological features do not separate this new genus from Parabalta Roewer or Pachyloides Holmberg (to which the species was formerly combined), male genitalic features, especially the shape of the ventral process of stylus, differ clearly. In turn, penis morphology suggests the systematic relationship of Qorimayus gen. nov. with the Chilean genera Metabalta Roewer and Nanophareus Roewer. A cladistic analysis was performed to test the phylogenetic affinities of the new genus; 28 terminals were used, comprising selected species of Parabalta, Pachyloides, Metabalta and Nanophareus, as well as other Gonyleptidae to represent the ‘subtropical’ and the ‘Chilean’ opiliofaunistic elements; the most external outgroups included one cosmetid, one metasarcid and one nomoclastid. Results supported the recognition of Qorimayus as an independent genus, and its close relationship with the Chilean genera Metabalta and Nanophareus. A detailed redescription of Qorimayus alticola comb. nov., along with some habitat notes are given. The presumed zoogeographical links of this endemic species with the central Chilean opiliofauna are briefly discussed.